IMPROVING LITERACY SKILLS THROUGH THE LEARNING MODEL CHILD FIND IT IN CLASS IV SDN CIBEBER 1 CIMAHI - Ruli Setiyadi; Naila Kurnia Restu (PrimaryEdu : Journal of Primary Education, 2018)
The research titled improving literacy skills through the learning model child find it in class iv sdn cibeber 1 cimahi based on the reduction of children ability in literacy skill in class IV. The method used in this research is Mix Method method (mixed qualitative and quantitative method) by comparing the learning outcomes of children before and after treatment. This research was conducted at SDN Cibeber 1 in South Cimahi District, Cimahi City. The results of this study is the increased ability to speak children as much as 70% after being given treatment find it. This shows that finding it can help improve children's literacy skills.